Occurrence of Mycorrhizal Fungi in Certain Medicinally/Economically Important Plants Growing in their Natural Habitat - Anilkumar, K. K.; Muraleedharakurup, G. (Indian Forester, 2010)
Field studies were conducted to examine whether the plants growing naturally in their habitat have a mycobiont in roots. A sum total of 106 angiospermic plants, which are of great economic/medicinal value, were randomly collected from different regions of Kottayam district, Kerala. It was found that 5 plants do not have any kind of mycorrhiza and they are herbaceous plants with low growth rate. Thirty eight plants have ectomycorrhiza, Ninety six plants have endomycorrhiza and Thirty three have both types of mycorrhiza in their root systems. The mycorrhizal fungus acts as a link species between two plants.